IKLIM SEKOLAH DI SMKN 1 PAPALANG KABUPATEN MAMUJU - irwan, irwan (Eklektika: Jurnal Pemikiran dan Penelitian Administrasi Pendidikan, 2016)
This research aimed at discovering the description of school climate at SMKN 1 Papalang in Mamuju district, factor which influence it, and the impact of the school climateThis research applied qualitative descriptive reseach conducted in SMKN 1 Papalang of Mamuju District. The sample was taken by purposive sampling technique. The data were coolected from the pricipal, teachers, students, studentsparents, head of the commentation through interviuw, observation, and documentation. The data were analyzed by conducting data reduction, data display, and conclosion drawing or verificaton.The result of the research revealed that the school climate of SMKN 1 Papalang of Mamuju Distrct viewed from the aspect of security, teaching and learning, interpersonal correlation, and institutional correlation had been conducted well. The factors which influence the school climate were enforcement of rules and regulations, sufficient teachers and staff, sufficient equipmentand material for learning; whereas, the inhibiting factors were limited funds, no guidance and counseling teacher, and teachers with no linear background of study. The impacts of the school climate were safe and comfortable school, students were disclipline, teaching process ran smoothly, kinship as wellas high competitive students and alumni